Validation of expanded form of lubben social network scale among community-dwelling geriatric population in India - K Bincy; Muthunarayan Logaraj; V V Anatharaman (Wolters Kluwer Medknow Publications, 2022)
Background: For assessing social networks in the elderly and the social support they receive and to predict social isolation, a proper valid and reliable short-scale screening tool is necessary. The present study aims to estimate the internal consistency and structural validity of the Lubben Social Network Scale (LSNS-18) among community-dwelling Indian older adults. Materials and Methods: We have administered the LSNS-18 scale to 500 older adults (>60 years) and performed confirmatory factor analysis (CFA) and structural equation modeling for the validation. Cronbach's alpha was done for estimating the internal consistency. Results: The LSNS-18 was easily answerable and the only minimum time is required for administration. CFA identified three domains with six items for each domain that demonstrated a good fit for the older adults with the internal consistency of 0.91. Conclusion: These findings suggest that LSNS-18 may be a valid tool for assessing the social network of the elderly and help to predict the risk for isolation in this vulnerable group.